Control of the synthesis of alkaline phosphatase and the phosphate-binding protein in Escherichia coli. - Willsky, G R (1976)
Using sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunological techniques, we have compared the synthesis of the phoA protein (alkaline phosphatase) and the phoS protein (phosphate-binding protein) in response to the level of phosphate in the medium in different genetic backgrounds containing the known alkaline phosphatase control mutations. Both proteins are produced in excess phosphate media in a phoR1a- strain, whereas neither protein is produced in a phoB- strain even under derepression conditions. In four different phoR1c- strains, however, the phoA product cannot be detected in extracts of cells obtained from any growth condition, whereas the phoS product is produced in both excess and limiting phosphate media. It is not yet known if phoR1c- mutants are a special class of mutations within the phoB gene or whether they occur in a separate cistron involved in alkaline phosphatase regulation. From these results we conclude that the expression of the phoA gene is not always co-regulated with expression of the phoS gene product. We have determined that the phoS protein is a component of periplasmic protein band P4 described by Morris et al. (1974). The phoS product lacks sulfur-containing amino acids and is extractable by treatment with polymyxin sulfate. The other component of band P4 contains methionine and/or cysteine and is not extracted by polymyxin sulfate treatment. Like the phoS and phoA proteins, its synthesis is sensitive to the concentration of phosphate in the growth medium. In addition, the existence of a new class of periplasmic proteins synthesized at maximum rate in high phosphate media is demonstrated.